Source of stressors among medical students in Malaysia: a brief review - Abd. Rahim, Nour El Huda; Ismail, Soraya; Rusli, Mohammad Farhan; Mat Zin, Nora (Fakulti Perubatan dan Sains Kesihatan Universiti Putra Malaysia, 2021)
Introduction: This study aimed to identify the main sources of stressors among medical students in Malaysian public or private universities. Studies have shown that undergraduate students suffer from tremendous stress. Tertiary education has always been regarded as a highly stressful environment, especially for medical students. Method: A systematic literature review of the scientific articles on stressors in medical students were conducted. Various literature were searched through electronic databases, i.e. PubMed and SCOPUS published until December 2019 for articles bearing keywords; i) stress, ii) medical students, and iii) Malaysia. A total of eighteen articles were reviewed and data extracted. Results: The most common stressor was related to academic requirements that included tests and examinations. The other significant determinants consisted of psychological stress and personal factors. Conclusion: Studying medicine is highly stressful for undergraduate students. Although comparing various studies were difficult because of the differences in study design, instrument, number of stressors, etc.; this review gives the most recent published articles which included descriptive information that might be very useful for future research and management of stressors for medical students and education.